Obveznost vstopa v sistem DDV na področju povezanih oseb - Pozvek, Maruša (Javna uprava, 2022)
Slovenian Tax Authority announced in the Strategic Guidelines and Priorities of the Inspectorates or Inspections that in 2022, a significant part of the supervision will focus on VAT identification on the identification of taxpayers who have not identified themselves for VAT but based on the scope and type of activities should have, which also includes related parties. As a result, they started urging related parties to register for VAT based on the provision of Article 94 (5) of Slovenian VAT Act. In this specific case, the (non)existence of a legal basis for this kind of procedures should be argued. The area of related parties is the intersection between direct taxes (income and corporate income tax) and indirect taxes (VAT). The definition of related parties is important for VAT purposes in the case of summing up the taxable turnover of related parties in connection with the mandatory identification of taxpayers for VAT purposes.
Keywords: davčne utaje; davčni zavezanci; davčno pravo; davek na dodano vrednost; davki; identification; obdavčljivi promet; related parties; same-type supply of goods; services of the same nature; tax avoidance; tax evasion; taxable turnover; VAT